PREVALENCE OF POST-TRAUMATIC STRESS DISORDER AND RELATED FACTORS IN 112 EMPLOYEES IN THE 11th MONTH OF THE PANDEMİC - Çelen, Özge; Şimşek, Zeynep (Paramedik Eğitiminde Standardizasyon ve Akreditasyon Derneği, 2024)
Objectives: In this study, the prevalence of post-traumatic stress disorder and associated factors among 112 employees was determined in the 11th month of the COVID-19 pandemic, with the aim of preparing for pandemics expected to increase with climate change. Material and Methods: In this cross-sectional study, 440 paramedics randomly selected, and "Socio-demographic Information Form", "Life Events Checklist" and "Post Traumatic Stress Disorder Control Form" were used for data collection. Results: 49.5% of the participants were female and the mean age was 29.9±7.34. The prevalence of Post Traumatic Stress Disorder (PTSD) was 59.8%. Multiple regression analysis showed that approximately 25% of the total PTSD score was explained independently by general health situation and socio-demographic characteristics of paramedics, 27% by crisis management skills, long working hours, lack of equipment and traffic density, and 40% by difficult life events during their professional practice intervention such as gun injuries and being attacked by gunfire, sexual assault, brutal death and causing injury/death to another person from past traumatic experiences (p<0.05). Conclusion: Based on these findings, in order to prevent/control of PTSD in paramedics; it is thought that it would be beneficial to integrate mental health monitoring system into the health and safety program and to apply regular supervision and psycho- social support interventions for high-risk groups in terms of controlling individual and occupational factors of paramedics and to include them in health services’ disaster preparedness plans.

Amaç: Bu çalışmada iklim değişikliğiyle birlikte artması beklenen pandemilere hazırlık amacıyla, COVID-19 pandemisinin 11. ayında 112 çalışanlarında travma sonrası stres bozukluğu prevalansı ve ilişkili faktörler saptanmıştır. Gereç ve Yöntemler: Kesitsel tipteki bu araştırmaya rastgele örnekleme yöntemiyle seçilen 440 paramedik katıldı. Veri toplamada "Sosyodemografik Bilgi Formu", "Yaşam Olayları Kontrol Listesi" ve "Travma Sonrası Stres Bozukluğu Kontrol Listesi" kullanıldı. Bulgular: Katılımcıların %49,5'i kadın ve yaş ortalaması 29,9±7,34 idi. Travma Sonrası Stres Bozukluğu (TSSB) yaygınlığı %59,8’dur. Çoklu regresyon analizi, toplam TSSB puanının yaklaşık %25'ini paramediklerin genel sağlık durumu ve sosyo-demografik özelliklerinin, %27'sini kriz yönetimi becerisi, uzun çalışma saatleri, ekipman eksikliği ve trafik yoğunluğunun, %40'ını ise travmatik yaşantılardan silah yaralanmalara, cinsel saldırıya, vahşice ölüme ve bir başkasının yaralanmasına/ ölümüne neden olan olaylara müdahale bağımsız olarak açıklamıştır (p<0.05). Sonuç: Bulgulara dayanarak paramediklerde TSSB'nin önlenmesi amacıyla; bireysel ve mesleki faktörlerin kontrolüne yönelik çalışan sağlığı ve güvenliği programlarına ruh sağlığı izleminin entegre edilmesinin, risk altındaki gruplara düzenli süpervizyon verilmesinin ve psiko-sosyal destek müdahalelerinin uygulanmasının, belirtilen girişimlerin afete hazırlık planlarına dahil edilmesinin yararlı olacağı düşünülmektedir.
PANDEMİNİN 11. AYINDA 112 ÇALIŞANLARINDA TRAVMA SONRASI STRES BOZUKLUĞU GÖRÜLME SIKLIĞI VE İLİŞKİLİ FAKTÖRLER
Keywords: Paramedics; Covid-19 Pandemia; Post Traumatic Stress Disorder; Traumatic Experiences; Individual and Occupational Factors; Paramedikler; Covid-19 Pandemisi; Travma Sonrası Stres Bozukluğu; Travmatik Yaşantılar; Kişi ve Ortam Faktörleri